Impact of Urban Landscape on Human Well-being as a Tool for Achievement of Sustainable Development - Moosavi, Mir Saeed; Jafari, Fatemeh; Davatgar Badie, Laleh (European Journal of Sustainable Development, 2018)
The urbanized world is facing unprecedented social-demographic, technological and environmental changes and in the face of these changes, an important set of questions arises related to how to plan and manage urban green spaces for the benefit of both urban dwellers and biodiversity. The diversity and quality of urban green spaces and human well-being are tightly linked as urban green areas provide a number of benefits for people. This study aimed to promote the characters of natural environment as a platform to enhance human well-being in urban areas and mainly was conducted to determine the need of urban community related to urban parks. The findings of this research can be used as guiding reference in related areas to improve and enhance the quality of public spaces in urban parks as an urban environment to fulfill the needs and requirements of visitors. Keywords: Landscape, Human, Sustainable, Urban.